Urology during a Crisis: A Management Algorithm - Papaefstathiou, Efstathios; Apostolopoulou, Aikaterini; Papaefstathiou, Eirini; Moysidis, Kyriakos; Hatzimouratidis, Konstantinos; Sarafis, Pavlos (Urology Journal, 2020)
COVID-19 pandemic has affected more than a million people worldwide causing a public health crisis. Under these unique circumstances, urologists continue to provide essential healthcare services and support healthcare systems, by participating in the treatment of COVID-19(+) patients and sparing vital equipment and hospital beds. However, delivering medical care during the pandemic requires strategic planning for all surgical and outpatient activities. Proposed measures include rescheduling elective non-oncological surgeries and using a prioritization protocol for oncological surgeries according to hospital capacity. Following that, outpatient clinics could be partly replaced by telemedicine. Additionally, urologists should be trained in screening and treating patients with COVID-19 during their daily routine. In order to efficiently provide their services, a management protocol for suspected or known COVID-19 urological patients should be implemented. Furthermore, preventive measures for the nosocomial dispersion of the virus and training on self-protective equipment is mandatory for all physicians. Finally, organizational planning for the best utilization of the staff is of utmost importance. Implementation and adaptation of the protocols according to local requirements and guidelines will ameliorate the quality of services and population’s health status. Finally, enhancement of current practices will prepare health systems for future crisis.